TINJAUAN YURIDIS TENTANG PERLINDUNGAN ANAK PELAKU TINDAK PIDANA PERBUATAN CABUL - Em Maimunnah (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACT The rapid development of information and tecnology  today and trigger the occurrence of criminal acts, inculding criminal acts of obscenity. Obscenity undertaken by minors is a very discriminating phenomenon, because the effects of susch immorality actions can lead to individual priblematics for the continuity and future development of children. The process of handling children with the category of obscenity can couse problems because they must be hendled legally the use of criminal justice system is considered the from of response to kriminal countermeasures and the from criminal law enforcement efforst. The results of this study show about how the regulation and legal protection for children  under the age of perpetrators of crime of fornication and how the procedure of the implemntation of criminal justice of children committing crime of fornications according to law No. 35 of 2014 on the amandement of law No. 23 of2012. Key Words: Child Protection, lewd